Multi-Objective Optimal Fuzzy Fractional-Order PID Controller Design - Hajiloo, Amir; Xie, Wen-Fang (Journal of advanced computational intelligence and intelligent informatics, 2014)
The design of the optimal fuzzy fractional-order PID controller is addressed in this work. A multi-objective genetic algorithm is proposed to design rule base and membership functions of the fuzzy logic systems. Three conflicting objective functions in both time and frequency domains have been used in Pareto design of the fuzzy fractional-order PID controller. The simulation results reveal the effectiveness of the proposed method in comparison with the results produced by the fractional-order PID controllers.